PENGEMBANGAN UMKM MELALUI PERAN SERTA STRATEGI DINAS KOPERASI DAN USAHA MIKRO KABUPATEN JOMBANG - Aminatul Maghfiroh; Lilik Rahmawati (Sekolah Tinggi Pariwisata Mataram, 2021)
In developing MSMEs, it is necessary to have an important role and strategy to help business actors in developing their businesses, but there are still many business actors who are still unable to develop their businesses properly and need assistance from the Cooperatives and Micro Business Office. The research method used is descriptive qualitative, namely by providing an overview and explanation of the Department of Cooperatives and Micro Enterprises in developing Jombang SMEs. The process of collecting data using interviews, observation and documentation. The focus of this research is the Role and Strategy of the Department of Cooperatives and Micro Enterprises in developing MSMEs to the fullest. The results of this study indicate that the Role and Strategy of the Department of Cooperatives and Micro Enterprises in developing MSMEs. The role of the Cooperative Service is that business actors can receive training, guidance and increase in knowledge and abilities, assist in financial terms, meaning by giving direction to business actors to obtain assistance funds from various parties, and making regulations and policies so that business actors can optimize their business. Meanwhile, the strategy used through market development is by involving business actors at exhibitions and helping promote their products on various social media accounts, participating in training and coaching activities held, and increasing financial capacity by providing direction for business actors to obtain business capital loans.